Collaboration and prospective memory: comparing nominal and collaborative group performance in strangers and couples. Issue 9 (21st October 2018) - Browning, Catherine A.; Harris, Celia B.; Van Bergen, Penny; Barnier, Amanda J.; Rendell, Peter G.
ABSTRACT: To perform prospective memory (PM) tasks in day-to-day life, we often enlist the help of others. Yet the effects of collaboration on PM are largely unknown. Adopting the methodology of the "collaborative recall paradigm", we tested whether stranger dyads (Experiment 1) and intimate couples (Experiment 2) would perform better on a "Virtual Week" task when working together or each working separately. In Experiment 1, we found evidence of collaborative inhibition: collaborating strangers did not perform to their pooled individual potential, although the effect was modulated by PM task difficulty. We also found that the overall collaborative inhibition effect was attributable to both the retrospective and prospective components of PM. In Experiment 2 however, there was no collaborative inhibition: there was no significant difference in performance between couples working together or separately. Our findings suggest potential costs of collaboration to PM. Intimate relationships may reduce the usual costs of collaboration, with implications for intervention training programmes and for populations who most need PM support.